Relative bioavailability of diazoxide, manufactured at two different international locations, in healthy participants under fasting conditions: an open-label, two-stage, adaptive, sequential two-period crossover study - Martin Otto Behm; Jialin Xu; Deborah Panebianco; Paul Fackler (SpringerOpen, 2017)
Abstract Theoretically, calculating the sample size required for achieving the desired power is straightforward with true coefficient of variance (CV) estimates and true test/reference geometric mean ratios (GMRs) of selected parameters. However, true variance estimates are often not known and are, instead, based on published literature or pilot trials. An open-label, two-stage, adaptive, sequential two-period crossover study was used to determine relative bioavailability of a single 100 mg dose of diazoxide manufactured at two different international sites. This design was utilized due to the lack of intra-subject variance estimation data for diazoxide pharmacokinetic parameters. Second-stage sample size was estimated using intra-participant variance from the first stage. Thirty-six healthy adults (age, 18-55 years) were randomized (1:1) to receive a single dose of test/reference product, a single dose of diazoxide (100 mg capsule), under fasting conditions with crossover after 14 days. GMRs (90% confidence interval [CI]) of area under curve from time zero to infinity (AUC0-inf) and maximum plasma concentrations (Cmax) of test versus reference product were 1.06 (1.03-1.10) and 1.17 (1.14-1.20), respectively. Bioequivalence was declared at stage 1 because 90% CIs were between 0.80 and 1.25; stage 2 was not initiated since the estimated power was >99% for both AUC0-inf and Cmax. Results of this study demonstrate efficient use of an adaptive, two-stage sequential design to assess bioequivalence. Similar study design may be effectively used in other bioequivalence studies wherein CV and GMRs of relevant parameters are unknown and sample size estimation is difficult.